Management of Statin Intolerance in 2018: Still More Questions Than Answers - Toth, Peter P. (Am J Cardiovasc Drugs, 2018)
Statin therapy is generally well tolerated and very effective in the prevention and treatment of cardiovascular disease, regardless of cholesterol levels; however, it can be associated with various adverse events (myalgia, myopathy, rhabdomyolysis, and diabetes mellitus, among others). Patients frequently discontinue statin therapy without medical advice because of perceived side effects and consequently increase their risk for cardiovascular events. In patients with statin intolerance, it may be advisable to change the dose, switch to a different statin, or try an alternate-day regimen. If intolerance is associated with all statins—even at the lowest dose—non-statin drugs and certain nutraceuticals can be considered. This review focuses on the definition of statin intolerance and on the development of clinical and therapeutic strategies for its management, including emerging alternative therapies.